Dose–volume histogram analysis of brainstem necrosis in head and neck tumors treated using carbon-ion radiotherapy. Issue 1 (October 2017) - Shirai, Katsuyuki; Fukata, Kyohei; Adachi, Akiko; Saitoh, Jun-ichi; Musha, Atsushi; Abe, Takanori; Kanai, Tatsuaki; Kobayashi, Daijiro; Shigeta, Yuka; Yokoo, Satoshi; Chikamatsu, Kazuaki; Ohno, Tatsuya; et al.
Abstract: Background and purpose: We aimed to evaluate the relationship between brainstem necrosis and dose–volume histograms in patients with head and neck tumors after carbon-ion radiotherapy. Material and methods: We evaluated 85 patients with head and neck tumors who underwent carbon-ion radiotherapy and were followed-up for ≥12 months. Brainstem necrosis was evaluated using the Common Terminology Criteria for Adverse Events (version 4.0). Results: The median follow-up was 24 months, and four patients developed grade 1 brainstem necrosis, with 2-year and 3-year cumulative rates of 2.8% and 6.5%, respectively. Receiver operating characteristic curve analysis revealed the following significant cut-off values: a maximum brainstem dose of 48 Gy (relative biological effectiveness [RBE]), D1 cm 3 of 27 Gy (RBE), V40 Gy (RBE) of 0.1 cm 3, V30 Gy (RBE) of 0.7 cm 3, and V20 Gy (RBE) of 1.4 cm 3 . Multivariate analysis revealed that V30 Gy (RBE) was most significantly associated with brainstem necrosis. The 2-year cumulative rates were 33% and 0% for V30 Gy (RBE) of ≥0.7 cm 3 and <0.7 cm 3, respectively ( p  < 0.001). Conclusions: The present study indicated that the dose constraints might help minimize brainstem necrosis after carbon-ion radiotherapy.